The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1523/jneurosci.15-06-04533.1995
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine-modulated potassium channels on rat striatal neurons: specific activation and cellular expression

Abstract: We have used cell-attached patch-clamp electrophysiology to characterize the activation and distribution of an 85 pS K+ channel on freshly dissociated rat striatal (caudate-putamen) neurons. In recordings from 643 cells, openings of this channel showed an absolute dependence on the presence of dopamine or the D2-like dopamine receptor agonist quinpirole in the cell-attached patch pipette, but were never seen when the D2 antagonist domperidone was applied along with quinpirole, or in the absence of drug. This c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
2

Year Published

1995
1995
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 22 publications
3
52
2
Order By: Relevance
“…4C). This result contrasts with observations of an 85 pS dopaminemodulated channel in caudate-putamen neurons, where we typically find two to four channels per patch under equivalent conditions (Greif et al, 1995). Consequently, there may be differences in channel or receptor distributions over the surface of the cell membrane between these two systems.…”
Section: Effects Of Opioid Receptor Activationcontrasting
confidence: 99%
See 4 more Smart Citations
“…4C). This result contrasts with observations of an 85 pS dopaminemodulated channel in caudate-putamen neurons, where we typically find two to four channels per patch under equivalent conditions (Greif et al, 1995). Consequently, there may be differences in channel or receptor distributions over the surface of the cell membrane between these two systems.…”
Section: Effects Of Opioid Receptor Activationcontrasting
confidence: 99%
“…We have not, however, been able to show that internal ATP gates the channel, because this channel proved unstable in inside-out recordings. However, our results are very similar to those for the 85 pS channel modulated by D 2 dopamine receptors in caudateputamen neurons (Greif et al, 1995). That channel is also activated by rotenone, is sensitive to sulfonylurea drugs in a manner suggestive of a K ATP channel (Lin et al, 1993), and has recently been shown to be directly regulated by ATP (Sun et al, 2000).…”
Section: Discussion the 130 Ps Channelsupporting
confidence: 86%
See 3 more Smart Citations